Efficacy and day 7 plasma piperaquine concentrations in African children treated for uncomplicated malaria with dihydroartemisinin-piperaquine. - Zongo, Issaka; Somé, Fabrice A; Somda, Serge A M; Parikh, Sunil; Rouamba, Noel; Rosenthal, Philip J; Tarning, Joel; Lindegardh, Niklas; Nosten, François; Ouédraogo, Jean Bosco (PloS one, 2014)
One promising new Artemisinin-based combination therapies (ACTs) is dihydroartemisinin-piperaquine (DHA-PQ). However, the pharmacokinetics of piperaquine and the relationship between drug levels and clinical efficacy are incompletely characterized, particularly in children.
Keywords: Antimalarials; Artemisinins; Burkina Faso; Child; Child, Preschool; Drug Administration Schedule; Drug Combinations; Female; Humans; Infant; Malaria, Falciparum; Male; Quinolines; Treatment Failure